The effect of repeated coffee mouth rinsing and caffeinated gum consumption on aerobic capacity and explosive power of table tennis players: a randomized, double-blind, placebo-controlled, crossover study - Azam Farmani; Mohammad Hemmatinafar; Maryam Koushkie Jahromi; Sepideh Pirmohammadi; Babak Imanian; Zeinab Jahan (Taylor & Francis Group, 2024)
ABSTRACTBackground Athletes require proper nutrition to enhance training and performance. Studies indicate that alternative sources of caffeine, such as caffeinated chewing gum, mouth rinses, energy gels, and coffee can improve performance. Therefore, this study investigated the impact of consuming caffeinated gum (CG) and repeated coffee mouth rinsing (CMR) on professional male table tennis players' aerobic capacity and explosive power.Method A randomized, cross-over, placebo-controlled, and double-blinded study was conducted with eighteen male table tennis players (Age: 21.86 ± 2.40 yr, Height: 173.80 ± 6.88 cm, Weight: 61.81 ± 10.32 kg). In each test session, the participants were randomly placed in one of the three conditions including i) Chewing caffeinated gum (CG, n = 6), ii) Coffee mouth rinsing (CMR, n = 6), iii) Starch capsule as a placebo (PLA, n = 6). All participants consumed caffeine with an average dose of ∼3 to 4.5 mg·kg−1. Also, a one-week interval was considered a washout period for each condition. First, the participants were given the required supplement and performed functional tests such as throwing medicine balls and Sargent's jump tests. Then, the maximum oxygen consumption (VO2max), time to exhaustion (TTE), oxygen consumption equivalent at primary ventilatory threshold (VO2 at VT1), and oxygen consumption equivalent at respiratory compensation point (VO2 at RCP) were measured during the Bruce test. All data were analyzed using SPSS Windows software, repeated measure analysis ANOVA, and Bonferroni post hoc tests at p < 0.05.Results The current study's findings illustrated that TTE significantly increased in CG (p = 0.000) and CMR (p = 0.012) conditions compared to PLA, but no significant difference was observed between CMR and CG (p = 1.00). VO2 at VT1 was significantly higher in CG (p = 0.004) and CMR (p = 0.000) compared to PLA; however, no significant difference was observed between CMR and CG (p = 0.335). VO2 at RCP increased significantly in CG (p = 0.000) and CMR (p = 0.000) compared to the PLA condition, and despite this, no significant difference was observed between CG and CMR (p = 1.000). Nevertheless, there were no significant differences between the three conditions in VO2max, throwing a medicine ball, and Sarjent's jump height.Conclusion The study found that CMR and CG had a relatively positive impact on male table tennis players' aerobic capacity; however, they did not significantly improve their explosive power.